Microneedle Enzyme Sensor Arrays for Continuous In Vivo Monitoring - Sanjiv Sharma (Enzymes as Sensors, 2017)
Microneedle enzyme sensors by virtue of their minimally invasive and hence pain-free penetration of skin allow for the measurement of metabolites, biomarkers, and drugs in the interstitial fluid that bathes the dermal tissue. Such devices if they are to be adopted widely into clinical practice need to be capable of delivering reliable measurements over extended periods of time (days) and to be fabricated by low-cost, scalable methods. Using injection molding of the base structures in polycarbonate, metal film deposition by sputtering and enzyme immobilization by electrodeposition can meet these requirements. The workflow to produce devices for clinical evaluation is then completed by sterilization and packaging. In vitro evaluation of the sensors’ response to varying analyte concentrations and their mechanical testing establish performance and safety characteristics. While most of the work is focused on glucose sensing, reflecting the significance of the global diabetes “epidemic,” the microneedles can also be used to measure lactate (another metabolite) and theophylline (a therapeutic drug).